The comparison of body awareness, difficulty in emotion regulation and self-management in panic and depressed patients with nonaffected persons - Masoumeh Kazempour; Parviz Sabahi (مجله علوم روانشناختی)
Background: A review of previous studies shows that, among the variables that affect the underlying mechanisms of panic and depression disorders, are body awareness, difficulty in emotional regulation, and patient's self-management. Considering the lack of research background on the comparison of the above three components in patients with panic and depression disorders, the present study seeks to answer the question whether these three components are different in patients with panic, depression and nonaffected persons? Aims: The purpose of this research was to compare body awareness, difficulty in emotion regulation and self-management among people with panic disorders, depression and nonaffected persons. Methods: The current research design was descriptive and causal-comparative. The statistical population of the research included all people suffering from panic disorders, depression and non-suffering people in the city of Babol in the autumn of 2022. The sampling method was available and the sample size was 30 people for each group. The data collection tools in this study included three body awareness questionnaires of Shields (1989), the difficulty in emotion regulation questionnaire of Gratz & Roemer (2004) and the self-management questionnaire of Houthun and Neck (2000). The collected data were analyzed by multivariate analysis of variance and Benferoni post hoc test using SPSS22 software. Results: The obtained results showed that there is no significant difference in body awareness between people suffering from panic disorders, depression and non-suffering people. There was no significant difference in other variables, including difficulty in emotion regulation and self-management, between the two panic and depressed groups, but both groups had a significant difference compared to the group of non-diseased people. It was also found that three groups of people suffering from panic, depression and non-suffering people have a significant difference in the three strategies of self-management, including behavioral strategies, natural reward and constructive thought pattern and difficulty in emotional regulation (P< 0.05). Conclusion: According to the obtained results, it can be concluded that people with panic disorders and depression have problems in emotion regulation and self-management compared to non-afflicted people. Therefore, it is suggested that psychiatrists and psychotherapists pay attention to the three variables of the present study in the therapeutic interventions of patients suffering from panic and depression in order to prevent the progression and exacerbation of disease symptoms.